Mitochondrial Causes of Epilepsy: Evaluation, Diagnosis, and Treatment - Steele, Hannah E.; Chinnery, Patrick F. (Seminars in Neurology, 2015)
Mitochondrial disorders are frequently associated with seizures. In this review, the authors discuss the seizure patterns and distinguishing features of mitochondrial epilepsy, alongside the indications for investigating, and how to investigate epilepsy from a mitochondrial perspective. Finally, they discuss management strategies for this complex group of patients.
Keywords: epilepsy; mitochondrial disease; investigation; diagnosis; treatment